Investigation of Transmission and Reflection of Single Mode Fiber Bragg Grating - Dedi Irawan; Saktioto; Azhar; Dwi Hanto; Bambang Widiyatmoko (Postgraduate, University of Mataram, 2024)
The use of Single Mode Fiber Bragg Grating (SMFBG) has been increasing in recent years due to its compact size, low cost, fast response and immunity to electromagnetic interference. It is commonly integrated into medical devices for long-distance light transmission and collection due to its high flexibility, low propagation loss, compatibility and tolerance to electromagnetic interference. SMFBG is a device made of thin glass material that is used as a medium for transmitting information in the form of light signals sourced from lasers or LEDs from one location to another. It consists of 3 main components, namely core with a certain grating, blanket (cladding) and jacket (coating). The advantage of optical fiber is that the data when transmitted is converted into light so as to reduce the risk of data damage. Other advantages include very small size, minimal interference with electromagnetic waves, resistance to temperature changes, attenuation when the transmission process is small enough, and large enough bandwidth. The orientation of this literature review is to understand the concept of optical fiber, the concept of reflection and refraction, and how light propagates in optical fiber.